Entrepreneurial impact : the role of MIT - an updated report - Roberts, Edward B.; Eesley, Charles E. (Foundations and trends in entrepreneurship, 2011)
The ultimate value of this study is to help us understand the economic impact of the entrepreneurial ventures of university graduates. We know that some universities play an important role in many economies through their core education, research and development, and other spillovers. However, in order to support economic growth through entrepreneurship, universities must create a culture and programs that make entrepreneurship widely accessible to students. While MIT's leadership in developing successful entrepreneurs has been evident anecdotally, this study -- one of the largest surveys of entrepreneur alumni ever conducted -- quantifies the significant impact of MIT's entrepreneurial ecosystem that supports firm start-ups. Furthermore, while MIT is more unique and unusual in the programs it offers and in its historical culture of entrepreneurship, MIT provides a benchmark by which other institutions can gauge the economic impact of their alumni entrepreneurs. The report also provides numerous examples of programs and practices that might be adopted, intact or modified as needed, by other universities that seek enhanced entrepreneurial development. The Appendix identifies several universities that have carried out surveys of alumni entrepreneurs